CT guided lung biopsy: Diagnostic yield and complications, using 18G coaxial semi-automatic core needle - Thapa, Ajit; Subedi, Kamal; Suwal, Sundar; Chataut, Dinesh (Nepal Journal of Medical Sciences, 2019)
Introduction: CT guided biopsy is essential for histopathological diagnosis of suspicious lung nodule, which are not amenable for either bronchoscopic or sonography guided sampling. Methods: Twenty eight patients with suspicious lung nodules not amenable for bronchoscopic or sonography guided sampling who underwent CT guided lung biopsy with 18 G coaxial semiautomatic core biopsy needle in one year were retrospectively studied for diagnostic yield and complications. Results: Out of 28 patients, who underwent CT guided lung nodule biopsy, 18 were male and 10 were female. The age ranged from 22 to 80 years. Lesion size ranged from one cm to four cm and depth of lesion from pleura ranged from zero cm to five cm. Diagnostic yield of our core needle biopsy was 26(92.3%). Clinically significant complication was low. Massive pneumothorax which needed intercostal drainage was 7.14% (2 patients). Pulmonary hemorrhage manifesting as hemoptysis was seen in 14.3 %( 2 patients). No hemothorax or air embolism was noted in any of the patient. Conclusion: CT guided lung lesion biopsy with 18 G coaxial semi-automatic core biopsy needle is a safe procedure with good diagnostic yield and relatively low incidence of clinically significant complications.